De l'amour - Stendhal 1783-1842; Martineau, Henri 1882-1958 (Paris Garnier frères, 1972)
'De l'amour' is one of his early works, a rational analysis of romantic passion that was based on his unrequited love for Mathilde, Countess Dembowska, whom he met while living at Milan.
Marie-Henri Beyle (1783-1842), better known by his pen name Stendhal was a 19th-century French writer. He is highly regarded for the acute analysis of his characters' psychology and considered one of the early and foremost practitioners of realism. A self-proclaimed egotist, he coined the same characteristic in his characters' "Beylism".
Keywords: 19th Century (1801-1900); Literature; Philosophy; France